Massive Ascites in Severe Pre-Eclampsia - Dah-Ching Ding; Senzen Hsu; Her-Young Su; Ta-Wei Chu (Elsevier, 2005)
Objective: To present a rare case of massive maternal ascites with severe pre-eclampsia at 35 weeks of gestation. Case Report: A 35-year-old, gravida 3, para 2, woman presented with a 1-day history of headache, blurred vision, and abdominal pain with uterine contractions, at 35 weeks of gestation. Ultrasonography showed a fetus that was small for gestational age. A large amount of free fluid was noted intraperitoneally. This complication developed in association with a blood pressure of 202/107 mmHg, proteinuria, and abnormal laboratory values. More than 2 L of ascitic fluid was removed at the time of cesarean section. Conclusion: Massive ascites is an unusual complication of pre-eclampsia that can result in respiratory compromise. The rarity of this condition may be due to under-reporting. Careful clinical and ultrasonographic examinations are necessary to detect this condition.